2012
DOI: 10.1007/s10456-012-9319-4
|View full text |Cite
|
Sign up to set email alerts
|

PET/SPECT imaging of hindlimb ischemia: focusing on angiogenesis and blood flow

Abstract: Peripheral artery disease (PAD) is a result of the atherosclerotic narrowing of blood vessels to the extremities, and the subsequent tissue ischemia can lead to the up-regulation of angiogenic growth factors and formation of new vessels as a recovery mechanism. Such formation of new vessels can be evaluated with various non-invasive molecular imaging techniques, where serial images from the same subjects can be obtained to allow the documentation of disease progression and therapeutic response. The most common… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 56 publications
0
46
0
Order By: Relevance
“…Radionuclide probes to image angiogenesis in hind limb ischemia include SPECT and PET-labeled RGDs or peptomimetic proteins. 9,[14][15][16][17] Experimental studies using these probes have shown that quantitative estimates of tracer uptake on scans in the affected limbs correlate well with capillary sprouting. We therefore chose to estimate angiogenesis at 5 days after FAL (peak time for capillary sprouting) with imaging.…”
Section: Discussionmentioning
confidence: 99%
“…Radionuclide probes to image angiogenesis in hind limb ischemia include SPECT and PET-labeled RGDs or peptomimetic proteins. 9,[14][15][16][17] Experimental studies using these probes have shown that quantitative estimates of tracer uptake on scans in the affected limbs correlate well with capillary sprouting. We therefore chose to estimate angiogenesis at 5 days after FAL (peak time for capillary sprouting) with imaging.…”
Section: Discussionmentioning
confidence: 99%
“…Molecular targeted imaging of angiogenesis has focused on EC targets (eg, VEGF, growth factor receptors, integrins, CD13, cell adhesion molecules), extracellular matrix proteins, and matrix proteases, or even associated non-EC targets (eg, monocytes, macrophages, and stem cells), and has been reviewed recently. [182][183][184] Several imaging modalities have been applied to evaluate angiogenesis and arteriogenesis in preclinical experimental animal models and are summarized in Table 7. Optical imaging approaches, in particular laser Doppler, have traditionally been used to evaluate changes in superficial perfusion associated with angiogenesis in models of hind-limb ischemia.…”
Section: Evaluation Of Microvascular Function Perfusion and Angiogementioning
confidence: 99%
“…2, 3 However, assessing the efficacy of pro-angiogenic treatment has been challenging due to the lack of reliable, non-invasive imaging methods. 4, 5 …”
Section: Introductionmentioning
confidence: 99%
“…5–7 Non-invasive molecular imaging methods can provide information on the response of the ischemic tissues to the treatment, as well as detect molecular abnormalities that contribute to the early pathogenesis, thereby permitting early intervention. Positron emission tomography (PET) is a non-invasive, sensitive, and quantitative radionuclide-based imaging modality, 8, 9 which can be used to detect molecular changes during ischemia.…”
Section: Introductionmentioning
confidence: 99%